Analisis Potensi Wisata Desa dengan Kerangka 6A: Studi Kasus Desa Ngajum, Malang - Agung Yoga Asmoro; Thamrin B Bachri; Alditia Detmuliati (Media Wisata, 2020)
This study aims to map tourism potential both in terms of tourism products and markets as an initial step in developing tourism in Ngajum Village. This research is community-based research implemented using the Participatory Action Research approach. The analysis was carried out through 6A's tourism product component approach without disregarding the tourism market analysis. The findings of this study are that Ngajum Village had untapped tourism potentials. Weaknesses in the components of attractions and available packages will be resolved by developing artificial attraction on land A, the potential for ecotourism activities on land B, agro-tourism on people's coffee plantations, spiritual tourism in Padepokan Soerjo Alam, as well as the potential for factory tour collaborations with Greenfield Dairy Factory. These potentials must be designed in stages to obtain optimal outcomes for the community by involving the roles of BUMDES and Pokdarwis as the main actors. In the end, the amenities component is considerably good, while the activities will align with the development of the attraction. The accessibilities and ancillary services are in good condition